2004
DOI: 10.1007/s00259-003-1452-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroPET imaging of brain tumor angiogenesis with 18F-labeled PEGylated RGD peptide

Abstract: We have previously labeled cyclic RGD peptide c(RGDyK) with fluorine-18 through conjugation labeling via a prosthetic 4-[18F]fluorobenzoyl moiety and applied this [18F]FB-RGD radiotracer for alphav-integrin expression imaging in different preclinical tumor models with good tumor-to-background contrast. However, the unfavorable hepatobiliary excretion and rapid tumor washout rate of this tracer limit its potential clinical applications. The aims of this study were to modify the [18F]FB-RGD tracer by inserting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 28 publications
3
150
0
2
Order By: Relevance
“…To improve integrin α v β 3 binding affinity, the multivalent concept has been successfully used to prepare multimeric cyclic RGD peptides, such as E[c(RGDfK)] 2 and E{E[c(RGDfK)] 2 } 2 , for development of the integrin α v β 3 -targeted diagnostic ( 64 Cu, 99m Tc and 111 In) and therapeutic ( 90 Y and 177 Lu) radiotracers (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Different PKM linkers have been used to improve excretion kinetics of the radiolabeled peptides.…”
Section: Discussionmentioning
confidence: 99%
“…To improve integrin α v β 3 binding affinity, the multivalent concept has been successfully used to prepare multimeric cyclic RGD peptides, such as E[c(RGDfK)] 2 and E{E[c(RGDfK)] 2 } 2 , for development of the integrin α v β 3 -targeted diagnostic ( 64 Cu, 99m Tc and 111 In) and therapeutic ( 90 Y and 177 Lu) radiotracers (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Different PKM linkers have been used to improve excretion kinetics of the radiolabeled peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Third, tissue biodistribution is also important, as many molecular imaging agents elicit undesired uptake in organs such as the kidneys and liver. Chemical modifications, such as PEG, have been shown to reduce non-specific liver uptake (Chen et al 2004b). In addition, modifying the chemical properties of peptide sequences (Ekblad et al 2008), or increasing specificity by altering the binding affinity to other target family members (Wang et al 2007a) have been used to improve the tissue biodistibution of in vivo molecular imaging agents.…”
Section: The Process Of Developing Phage-derived In Vivo Molecular Immentioning
confidence: 99%
“…Second, rapid clearance is desired to obtain minimal background levels for molecular imaging applications; however, this must be balanced with the ability to elicit specific uptake in desired tissue. Chemical modifications with polyethylene glycol (PEG) or albumin binding peptides have been used to increase circulation time and enhance pharmacokinetic profiles (Chen et al 2004b). In addition, peptides with higher target binding affinity (Kimura et al 2009a) and multivalent target binding (Liu 2006) have been shown to elicit increased imaging signals compared to weaker binding and monomeric peptides; yet, in some cases monovalent proteins have been shown to exhibit better tumor uptake compared to higher affinity dimeric versions (Cheng et al 2008).…”
Section: The Process Of Developing Phage-derived In Vivo Molecular Immentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Although these agents can be exquisitely specific for a v b 3 -integrin, their penetration beyond the circulation allows binding to a cadre of nonendothelial sources. The biodistribution of perfluorocarbon NP to reticuloendothelial (RES) organs is well-known and previously reported, 12 but the potential for higher radionuclide payloads and their intravascular distribution make them attractive agents for rapid identification of nascent tumors in non-RES regions, including the brain, head and neck, lung, breast and prostate.…”
Section: In or 99mmentioning
confidence: 99%